A kind of anti-aging ABS plastic and preparation method thereof

By chemically bonding nanotitanium dioxide to hindered phenol antioxidants, a new aging-resistant composite particles are formed, which solves the problem of degradation and aging of ABS plastics in long-term light conditions, improves its aging resistance and mechanical properties, and is suitable for a variety of application scenarios.

CN119307064BActive Publication Date: 2025-03-14GUANGZHOU BAIYUN CLEANING PRODS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411662991.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Existing ABS plastics are prone to degradation, aging and discoloration, and even cracking under long-term lighting conditions, resulting in insufficient aging resistance.

Method used

By chemically bonding nanotitanium dioxide to hindered phenol antioxidants, a new aging-resistant composite particles are formed, and maleic anhydride is used as a bridge to combine the advantages and disadvantages of inorganic aging-resistant agents and organic antioxidants to improve the aging resistance of ABS plastics.

Benefits of technology

It improves the aging resistance and mechanical properties of ABS plastic, reduces the content of unsaturated double bonds, and enhances the bonding strength between composite particles and ABS plastic. It is suitable for cleaning tools and outdoor plastic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143923110000071
    Figure BDA0005143923110000071
Patent Text Reader

Abstract

The present invention is based on the research of the prior art and combines some shortcomings of the current ABS plastic. Provides an anti-aging ABS plastic and a preparation method thereof. The present invention combines the respective advantages and disadvantages of inorganic anti-aging agents and organic antioxidants, uses maleic anhydride as a bridge, chemically bonds nano titanium dioxide and hindered phenol antioxidants, and forms a new type of anti-aging composite particles, which have the characteristics of good aging resistance and good anti-migration. The anti-aging composite particles obtained by the present invention contain carbon-carbon double bonds, which can polymerize with the residual double bonds in ABS under heating conditions and the action of free radicals, reduce the content of unsaturated double bonds in ABS molecules, and further improve its anti-aging and mechanical properties. The ABS plastic obtained by the present invention has excellent anti-aging and mechanical properties, is suitable for cleaning tools such as trash cans, cleaning vehicles, cleaning equipment, etc., and is also suitable for outdoor plastic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anti-aging plastic and a preparation method thereof, in particular to an anti-aging ABS plastic and a preparation method thereof. Background Art

[0002] ABS plastic, also known as acrylonitrile-butadiene-styrene copolymer, is a thermoplastic polymer with excellent performance obtained by copolymerizing acrylonitrile, butadiene and styrene. The acrylonitrile component in ABS reflects heat resistance, chemical resistance, rigidity and tensile strength, butadiene can provide impact resistance, and styrene can improve fluidity and gloss. These three components are combined with each other and complement each other. The prepared ABS plastic has excellent impact strength, heat resistance, low temperature resistance, chemical resistance and electrical properties. With excellent comprehensive performance, it is currently the polymer with the largest output and the most widespread application. The application areas of ABS plastic include life, automobiles, electronic appliances, etc., and the application areas are very wide.

[0003] ABS plastic is a thermoplastic polymer. With the expansion of its application field, the requirements for its aging resistance are getting higher and higher. Due to the presence of unsaturated carbon-carbon double bonds in the molecular structure, ABS plastic is prone to degradation, aging, discoloration, and even cracking under long-term light conditions. Therefore, the improvement of ABS aging resistance has always been one of the technical hotspots that people generally study. For the improvement of aging resistance, antioxidants, ultraviolet absorbers, light stabilizers, etc. are usually added. Antioxidants are divided into hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants based on their antioxidant mechanism. Ultraviolet absorbers include salicylic acid esters, benzophenone derivatives, benzotriazole, etc., and light stabilizers mainly include hindered amine light stabilizers.

[0004] Patent CN102516699A discloses an ABS weather-resistant and anti-aging functional masterbatch: it includes AS powder, ABS high-rubber powder, nano-oxide, antioxidant, ultraviolet absorber, and processing aid. Adding the functional masterbatch of the invention to ABS can greatly improve the anti-aging and weather-resistant properties of ABS.

[0005] Patent CN103351572A discloses an anti-aging ABS-PMMA plastic alloy. The application concludes through a large number of experiments that the three anti-aging agents, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane and distearyl thiodipropionate, are rationally compounded and used to achieve synergistic effects and obvious anti-aging effects.

[0006] Patent CN105566839A discloses a high-performance, aging-resistant ABS / GF composite material and a preparation method thereof. It is a more excellent and practical ABS / GF composite material composition and a manufacturing method thereof. By adding a compatibilizer SAG containing a glycidyl methacrylate (GMA) group, the mechanical properties, processing properties and aging resistance of the material are improved, the processing is simpler and the production cost is lower.

[0007] Although people have conducted extensive research on the aging resistance of ABS plastics, there are still deficiencies in the compounding of inorganic and organic anti-aging agents, the research on reactive anti-aging agents, the compounding of hindered phenol antioxidants and phosphite antioxidants, and the synergistic research on UV absorbers and light stabilizers.

[0008] The present invention is based on the research of the prior art and combines some shortcomings of the current ABS plastic. Provides an anti-aging ABS plastic and a preparation method thereof. The present invention mainly studies the preparation of anti-aging composite particles and the effect of their addition on the anti-aging properties and mechanical properties of the obtained ABS plastic. The present invention combines the respective advantages and disadvantages of inorganic anti-aging agents and organic antioxidants, uses maleic anhydride as a bridge, chemically bonds nano titanium dioxide and hindered phenol antioxidants, and forms new anti-aging composite particles, which have the characteristics of good aging resistance and good anti-migration. The anti-aging composite particles obtained by the present invention contain carbon-carbon double bonds, which can polymerize with the residual double bonds in ABS under heating conditions and the action of free radicals, thereby grafting the anti-aging composite particles into the ABS molecules, reducing the content of unsaturated double bonds in the ABS molecules, improving the bonding strength between the anti-aging composite particles and the ABS plastic, and further improving its anti-aging and mechanical properties. The ABS plastic obtained by the present invention has excellent aging resistance and mechanical properties, is suitable for cleaning tools such as trash cans, cleaning vehicles, cleaning equipment, etc., and is also suitable for outdoor plastic products. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides an anti-aging ABS plastic and a preparation method thereof. The method combines the advantages and disadvantages of inorganic anti-aging agents and organic antioxidants, uses maleic anhydride as a bridge, chemically bonds nano titanium dioxide and hindered phenol antioxidants, and forms a new type of anti-aging composite particles, which have the characteristics of good aging resistance and good anti-migration. The anti-aging composite particles obtained by the present invention contain carbon-carbon double bonds, which can polymerize with the residual double bonds in ABS under heating conditions and the action of free radicals, thereby grafting the anti-aging composite particles into ABS molecules, further improving its anti-aging and mechanical properties.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] An anti-aging ABS plastic, composed of the following raw materials in parts by weight:

[0012] ABS resin 100 parts

[0013] 5-15 parts of anti-aging composite particles

[0014] 3-8 parts of antioxidant

[0015] Flame retardant 5-12 parts

[0016] 3-6 parts of compatibilizer

[0017] Heat stabilizer 0.5-2 parts

[0018] The antioxidant is a phosphite antioxidant, preferably, the antioxidant is one or a combination of two or more of antioxidants 168, 626, and TNPP;

[0019] The flame retardant is one or a combination of aluminum hydroxide or magnesium hydroxide;

[0020] The compatibilizer is one or a combination of two or more of a terpolymer of methyl methacrylate-glycidyl methacrylate-ethyl acrylate, a graft of ABS, styrene-acrylonitrile-glycidyl methacrylate and a styrene-maleic anhydride copolymer;

[0021] The heat stabilizer is one of a lead salt heat stabilizer, a metal soap heat stabilizer or an organic tin heat stabilizer, or a combination of two or more thereof.

[0022] The preparation process of the aging-resistant composite particles is as follows:

[0023] Step 1:

[0024] Add 10-15 parts of nano titanium dioxide to 200-300 ml of a sodium hydroxide aqueous solution with a mass fraction of 5-10 wt%, stir in a water bath at 60-70° C. for 4-5 hours, cool to room temperature after the reaction, filter, wash with water, and dry at 70-80° C. for 10-12 hours to obtain surface hydroxylated nano titanium dioxide;

[0025] Step 2:

[0026] Add 1-3 parts of an amino-containing silane coupling agent to 30-50 ml of a 90 wt% ethanol aqueous solution for hydrolysis, and adjust the pH value of the ethanol aqueous solution to 8-10 with a pH adjuster, and hydrolyze for 3-4 hours to obtain a hydrolyzed solution;

[0027] Step 3:

[0028] Adding the surface hydroxylated nano-titanium dioxide prepared in step 1 to the hydrolysis solution prepared in step 2; reflux reaction for 2-3 hours under stirring conditions, filtering, washing, and drying to obtain aminosilane coupling agent-modified nano-titanium dioxide;

[0029] Step 4:

[0030] Add 8-12 parts of the aminosilane coupling agent modified nano titanium dioxide prepared in step 3 into 100-300 ml of tetrahydrofuran, stir and disperse evenly to obtain a dispersion, add 2-5 parts of 2,6-di-tert-butyl-4-aminophenol, 4-8 parts of maleic anhydride, and 0.5-1 part of triethylamine to the dispersion, react at 60-70°C for 4-5h, cool to room temperature after the reaction, filter, and dry to obtain the aging-resistant composite particles.

[0031] The amino-containing silane coupling agent in step 2 is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

[0032] The pH regulator in step 2 is sodium hydroxide or potassium hydroxide.

[0033] The preparation method of the anti-aging ABS plastic comprises the following steps:

[0034] 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 5-10 minutes to form a primary mixture;

[0035] 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 5-10 minutes to form a secondary mixture;

[0036] 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 180-220° C. to obtain anti-aging ABS plastic.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention combines the advantages and disadvantages of inorganic anti-aging agents and organic antioxidants, uses maleic anhydride as a bridge, chemically bonds nano titanium dioxide and hindered phenol antioxidants, and forms new anti-aging composite particles, which have the characteristics of good aging resistance and good anti-migration. The anti-aging composite particles obtained by the present invention contain carbon-carbon double bonds, which can polymerize with the residual double bonds in ABS under heating conditions and the action of free radicals, thereby grafting the anti-aging composite particles into the ABS molecules, reducing the content of unsaturated double bonds in the ABS molecules, improving the bonding strength between the anti-aging composite particles and the ABS plastic, and further improving its anti-aging and mechanical properties. In addition, the present invention also studies the synergistic performance of the obtained anti-aging composite particles and phosphite auxiliary antioxidants. DETAILED DESCRIPTION

[0039] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0040] Preparation Example 1

[0041] The preparation process of the aging-resistant composite particles is as follows:

[0042] Step 1:

[0043] Add 10 parts of nano titanium dioxide into 250 ml of 6 wt% sodium hydroxide aqueous solution, stir in a water bath at 60°C for 5 hours, cool to room temperature after the reaction, filter, wash with water, and dry at 80°C for 10 hours to obtain surface hydroxylated nano titanium dioxide;

[0044] Step 2:

[0045] 2 parts of γ-aminopropyltriethoxysilane were added to 30 ml of 90 wt% ethanol aqueous solution for hydrolysis, and the pH value of the ethanol aqueous solution was adjusted to 8 with sodium hydroxide, and the hydrolysis was performed for 3 hours to obtain a hydrolyzed solution;

[0046] Step 3:

[0047] Adding the surface hydroxylated nano-titanium dioxide prepared in step 1 to the hydrolysis solution prepared in step 2; reflux reaction for 2 hours under stirring, filtering, washing and drying to obtain aminosilane coupling agent-modified nano-titanium dioxide;

[0048] Step 4:

[0049] Add 8 parts of the aminosilane coupling agent modified nano titanium dioxide prepared in step 3 into 200 ml of tetrahydrofuran, stir and disperse evenly to obtain a dispersion, add 3 parts of 2,6-di-tert-butyl-4-aminophenol, 4 parts of maleic anhydride, and 0.5 parts of triethylamine to the dispersion, react at 60°C for 4.5 hours, cool to room temperature after the reaction, filter, and dry to obtain the aging-resistant composite particles A.

[0050] Preparation Example 2

[0051] The preparation steps are the same as those in Preparation Example 1, except that the preparation and addition of aminosilane coupling agent-modified nano-titanium dioxide are omitted, thereby obtaining the aging-resistant composite particles B.

[0052] Preparation Example 3

[0053] The preparation steps are the same as those in Preparation Example 1, except that the addition of 2,6-di-tert-butyl-4-aminophenol is omitted, thereby obtaining the aging-resistant composite particles C.

[0054] Preparation Example 4

[0055] The preparation steps are the same as those in Preparation Example 1, except that the addition of maleic anhydride is omitted, thereby obtaining the aging-resistant composite particles D.

[0056] Example 1

[0057] Preparation of anti-aging ABS plastic:

[0058] The composition of each component raw material is calculated by the following weight parts:

[0059] ABS resin 100 parts

[0060] Anti-aging composite particles A 6 parts

[0061] Antioxidant 168 4 parts

[0062] 5 parts of aluminum hydroxide

[0063] 3 parts of styrene-maleic anhydride copolymer

[0064] 0.5 parts of lead salt heat stabilizer

[0065] The specific preparation process of anti-aging ABS plastic is as follows:

[0066] 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 6 minutes to form a primary mixture;

[0067] 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 8 minutes to form a secondary mixture;

[0068] 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 200° C. to obtain anti-aging ABS plastic.

[0069] Example 2

[0070] Preparation of anti-aging ABS plastic:

[0071] The composition of each component raw material is calculated by the following weight parts:

[0072] ABS resin 100 parts

[0073] Anti-aging composite particles A 8 parts

[0074] Antioxidant 168 5 parts

[0075] 8 parts of aluminum hydroxide

[0076] 4 parts of styrene-maleic anhydride copolymer

[0077] 0.5 parts of lead salt heat stabilizer

[0078] The specific preparation process of anti-aging ABS plastic is as follows:

[0079] 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 8 minutes to form a primary mixture;

[0080] 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 10 minutes to form a secondary mixture;

[0081] 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 210° C. to obtain anti-aging ABS plastic.

[0082] Example 3

[0083] Preparation of anti-aging ABS plastic:

[0084] The composition of each component raw material is calculated by the following weight parts:

[0085] ABS resin 100 parts

[0086] Anti-aging composite particles A 6 parts

[0087] 4 parts of antioxidant TNPP

[0088] 5 parts of aluminum hydroxide

[0089] 3 parts of styrene-maleic anhydride copolymer

[0090] 0.5 parts of lead salt heat stabilizer

[0091] The specific preparation process of anti-aging ABS plastic is as follows:

[0092] 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 6 minutes to form a primary mixture;

[0093] 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 8 minutes to form a secondary mixture;

[0094] 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 200° C. to obtain anti-aging ABS plastic.

[0095] Comparative Example 1

[0096] Preparation of anti-aging ABS plastic:

[0097] The composition of each component raw material is calculated by the following weight parts:

[0098] ABS resin 100 parts

[0099] Anti-aging composite particles B 6 parts

[0100] Antioxidant 168 4 parts

[0101] 5 parts of aluminum hydroxide

[0102] 3 parts of styrene-maleic anhydride copolymer

[0103] 0.5 parts of lead salt heat stabilizer

[0104] The specific preparation process of anti-aging ABS plastic is as follows:

[0105] 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 6 minutes to form a primary mixture;

[0106] 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 8 minutes to form a secondary mixture;

[0107] 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 200° C. to obtain anti-aging ABS plastic.

[0108] Comparative Example 2

[0109] Preparation of anti-aging ABS plastic:

[0110] The composition of each component raw material is calculated by the following weight parts:

[0111] ABS resin 100 parts

[0112] Anti-aging composite particles C 6 parts

[0113] Antioxidant 168 4 parts

[0114] 5 parts of aluminum hydroxide

[0115] 3 parts of styrene-maleic anhydride copolymer

[0116] 0.5 parts of lead salt heat stabilizer

[0117] The specific preparation process of anti-aging ABS plastic is as follows:

[0118] 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 6 minutes to form a primary mixture;

[0119] 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 8 minutes to form a secondary mixture;

[0120] 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 200° C. to obtain anti-aging ABS plastic.

[0121] Comparative Example 3

[0122] Preparation of anti-aging ABS plastic:

[0123] The composition of each component raw material is calculated by the following weight parts:

[0124] ABS resin 100 parts

[0125] Anti-aging composite particles D 6 parts

[0126] Antioxidant 168 4 parts

[0127] 5 parts of aluminum hydroxide

[0128] 3 parts of styrene-maleic anhydride copolymer

[0129] 0.5 parts of lead salt heat stabilizer

[0130] The specific preparation process of anti-aging ABS plastic is as follows:

[0131] 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 6 minutes to form a primary mixture;

[0132] 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 8 minutes to form a secondary mixture;

[0133] 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 200° C. to obtain anti-aging ABS plastic.

[0134] Performance Testing

[0135] After the ABS plastic materials prepared in Examples 1-3 and Comparative Examples 1-3 were prepared into standard specimens, their properties were tested, including tensile strength (reference standard ASTM D638), flexural strength (reference standard ASTM D790), impact strength (reference standard ASTM D256, 23°C), and heat deformation temperature (reference standard ASTM D648, 1.8MPa); aging test: the specimens were placed in a xenon lamp aging box at 80°C for 1200 hours.

[0136] The results are shown in Table 1.

[0137] Table 1 Comparison of properties of different anti-aging ABS plastics

[0138]

[0139] From the experimental results in Table 1, it can be seen that the anti-aging ABS plastic prepared in the present application not only has high tensile strength, flexural strength, notched impact strength and heat deformation temperature, but also has high tensile strength retention rate and flexural strength retention rate after aging. Comparative Example 1 does not add nano-titanium dioxide modified by aminosilane coupling agent, Comparative Example 2 does not add 2,6-di-tert-butyl-4-aminophenol, and Comparative Example 3 does not add maleic anhydride. Compared with Example 1, the ABS plastics obtained in the three comparative examples have a certain degree of decline in the initial mechanical properties and the mechanical property retention rate after aging.

[0140] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the defined scope, they should all fall within the protection scope of the present invention.

Claims

1. An anti-aging ABS plastic, characterized in that: According to weight parts, it is composed of the following raw materials: ABS resin 100 parts 5-15 parts of anti-aging composite particles 3-8 parts of antioxidant Flame retardant 5-12 parts 3-6 parts of compatibilizer Heat stabilizer 0.5-2 parts The preparation process of the aging-resistant composite particles is as follows: Step 1: Add 10-15 parts of nano titanium dioxide to 200-300 ml of a sodium hydroxide aqueous solution with a mass fraction of 5-10 wt%, stir in a water bath at 60-70° C. for 4-5 hours, cool to room temperature after the reaction, filter, wash with water, and dry at 70-80° C. for 10-12 hours to obtain surface hydroxylated nano titanium dioxide; Step 2: Add 1-3 parts of an amino-containing silane coupling agent to 30-50 ml of a 90 wt% ethanol aqueous solution for hydrolysis, and adjust the pH value of the ethanol aqueous solution to 8-10 with a pH adjuster, and hydrolyze for 3-4 hours to obtain a hydrolyzed solution; Step 3: Adding the surface hydroxylated nano-titanium dioxide prepared in step 1 to the hydrolysis solution prepared in step 2; reflux reaction for 2-3 hours under stirring conditions, filtering, washing, and drying to obtain aminosilane coupling agent-modified nano-titanium dioxide; Step 4: Add 8-12 parts of the aminosilane coupling agent modified nano titanium dioxide prepared in step 3 into 100-300 ml of tetrahydrofuran, stir and disperse evenly to obtain a dispersion, add 2-5 parts of 2,6-di-tert-butyl-4-aminophenol, 4-8 parts of maleic anhydride, and 0.5-1 part of triethylamine to the dispersion, react at 60-70°C for 4-5h, cool to room temperature after the reaction, filter, and dry to obtain the aging-resistant composite particles.

2. The anti-aging ABS plastic according to claim 1, characterized in that: The antioxidant is one of antioxidants 168, 626, and TNPP, or a combination of two or more thereof.

3. The anti-aging ABS plastic according to claim 1, characterized in that: The flame retardant is one of aluminum hydroxide and magnesium hydroxide or a combination of the two.

4. The anti-aging ABS plastic according to claim 1, characterized in that: The compatibilizer is one or a combination of two or more of a terpolymer of methyl methacrylate-glycidyl methacrylate-ethyl acrylate, styrene-acrylonitrile-glycidyl methacrylate and a styrene-maleic anhydride copolymer.

5. The anti-aging ABS plastic according to claim 1, characterized in that: The heat stabilizer is one of a lead salt heat stabilizer, a metal soap heat stabilizer or an organic tin heat stabilizer, or a combination of two or more thereof.

6. The anti-aging ABS plastic according to claim 1, characterized in that: The amino-containing silane coupling agent in step 2 is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane.

7. The anti-aging ABS plastic according to claim 1, characterized in that: The pH regulator in step 2 is sodium hydroxide or potassium hydroxide.

8. A method for preparing an anti-aging ABS plastic according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) Weigh all the raw materials except the aging-resistant composite particles in proportion, add them into a high-speed mixer, and stir and mix for 5-10 minutes to form a primary mixture; 2) adding the anti-aging composite particles to the primary mixture in step 1, and continuing to stir and mix for 5-10 minutes to form a secondary mixture; 3) The secondary mixture is melted, extruded, granulated and dried at a processing temperature of 180-220° C. to obtain anti-aging ABS plastic.

Citation Information

Patent Citations

  • ABS (Acrylonitrile Butadiene Styrene) weather-resistant and anti-ageing functional master batch

    CN102516699A

  • Aging-resistant ABS (Acrylonitrile Butadiene Styrene)-PMMA (Polymethyl Methacrylate) plastic alloy

    CN103351572A

  • High-performance anti-aging ABS / GF composite material and preparation method thereof

    CN105566839A

  • Conductive antiaging ABS (acrylonitrile-butadiene-styrene) composite plastic and preparation method thereof

    CN105860420A

  • Anti-aging polypropylene furniture plastic particles and preparation method thereof

    CN114456495A